(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This study focuses on the declaration of bankruptcy in the new Bankruptcy Law, by examining the contents of the bankruptcy order, providing in-depth analysis of the different pronouncements of said order, which establish and determine the effects of bankruptcy on the debtor’s estate.